PENGEMBANGAN MEDIA POP UP BOOK TEMA 5 PAHLAWANKU PADA MODEL PEMBELAJARAN NUMBERED HEAD TOGETHER KELAS IV SDN 01 GINTUNG - Fitriani, Lutfi; Fajriyah, Khusnul (KALAM CENDEKIA PGSD KEBUMEN, 2018)
Abstract This study aims to determine the success of mining and media feasibility po up book on the model of learning Numbered Head Together. This type of research is research and delevopment (R & D) research. Research and development methods are used to produce specific products and test the validity of a medium. The subjects of this research are 26 students of grade IV of elementary school. The data collected in this study are data of media experts and material experts, and product trial data. The data collection instrument is a questionnaire. The product produced in this research is a pop up media that is designed using corel X.5. Data processing is taken from validation of media expert, material expert, student acceptance questionnaire, and teacher acceptance questionnaire. The result of data analysis on media expert validation is 93% very good, material expert 89% very good, student acceptance questionnaire 88% very good, teacher acceptance questionnaire 96%. It shows the effective pop-up medium used in learning. Based on the results of this development research, the suggestion that researchers can convey is that the pop-up media can be used by the teacher as one of the learning media in the school. Keywords: Pop Up Book, Numbered Head Together Abstrak Penelitian  ini  bertujuan  untuk  mengetahui  keberhasilan pengambangan dan kelayakan media po up book pada model pembelajaran Numbered Head Together.  Jenis penelitian  ini adalah penelitian research  and delevopment (R&D).  Metode  penelitian  dan  pengembangan  digunakan  untuk menghasilkan  produk  tertentu  dan menguji kevalidan suatu media. Subyek  penelitian  dalam  penelitian  ini  adalah  26 siswa  kelas  IV  Sekolah Dasar. Data  yang  dikumpulkan  dalam  penelitian  ini  adalah  data  ahli  media  dan  ahli materi, dan data ujicoba produk. Instrumen pengumpulan data berupa angket. Produk yang dihasilkan dalam penelitian ini adalah media pop up yang di desain menggunakan corel X.5. Pengolahan  data  diambil  dari  validasi  ahli media,  ahli materi,  angket keberterimaan siswa,  dan  angket keberterimaan guru. Hasil analisis  data  pada  validasi  ahli media 93% sangat baik, ahli materi 89% sangat baik, angket keberterimaan siswa 88% sangat baik, angket keberterimaan guru 96%. Hal ini  menunjukkan  media pop up efektif digunakan dalam pembelajaran. Berdasarkan  hasil  penelitian  pengembangan  ini,  saran  yang  dapat  peneliti sampaikan adalah media pop up dapat digunakan guru  sebagai  salah  satu media  pembelajaran  di  sekolah.Kata kunci: Pop Up Book, Numbered Head Together